Analysis of the Influence of Human Development Index, Unemployment Rate, and Minimum Wage on Poverty Rates in Regencies/Cities of Central Java Province in 2021 – 2025 - Ahmad Reza; Maulidyah Indira Hasmarini (STIE Amkop Makassar, 2026)
This study aims to analyze the effect of the Human Development Index (HDI), open unemployment rate, and minimum wage on poverty levels in regencies/cities in Central Java Province during the period 2021–2025. This research employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS) and is analyzed using panel data regression. The model selection was conducted through the Chow Test and Hausman Test, which indicate that the Fixed Effects Model (FEM) is the most appropriate model. The results show that all independent variables simultaneously have a significant effect on poverty levels, with a probability value of F-statistic of 0.000 and a coefficient of determination (R²) of 0.987. Partially, the open unemployment rate has a positive and significant effect on poverty, while the minimum wage has a negative and significant effect on poverty. Meanwhile, the Human Development Index (HDI) has a negative but insignificant effect on poverty levels. These findings suggest that job creation and appropriate wage policies play a crucial role in reducing poverty, while improvements in human development must be accompanied by adequate employment opportunities to achieve optimal outcomes.